Enhancing Efficiency, Reducing Length of Stay and Costs in Pediatric Cardiology Rounds Through Simulation-Based Optimization - Yang, Yifan; Fernandes-Junior, Silvio; Wongphothiphan, Thipkanok; Zhang, Xu; Hoffman, Jeffrey; Bowman, Jessica; Huang, Yungui (Applied Clinical Informatics, 2025)
Enhancing the efficiency of family-centered rounds (FCRs) while ensuring timely patient care has been a focus of study over the past decade. We employed an Operations Research technique (i.e., simulation) to identify opportunities for improving rounding efficiency on our inpatient cardiology unit at Nationwide Children's Hospital (NCH).Through simulation of schedule-based rounds, our aims were to reduce the length of stay (LOS) and subsequent healthcare costs via (1) prioritizing rounds for patients needing time-sensitive care decisions or those likely ready to be discharged, and (2) enhancing participation from both families and bedside nurses during rounds.Data were collected through direct observation of rounding activities. We then conducted simulations to evaluate the effect of various rounding paths on efficiency, measured in terms of time and penalties depending on context.Our simulations indicated a tradeoff between minimizing the risk of delayed rounding and the amount of time spent on rounds. Optimizing rounds for 20 patients reduced cumulative patient waiting time and associated penalty scores. Based on prior research linking earlier clinical interventions to improved efficiency, this approach is estimated to reduce LOS by 166.08 hours and cost by approximately $3,460 per rotation.By simulating the hospital rounding processes on an inpatient pediatric cardiology unit, we demonstrated that prioritized rounding could reduce both LOS and associated costs. Despite a potential increase in total rounding time, which can be managed by clinical decision-makers, we recommend utilizing scheduling-based FCRs based on prioritization techniques that enhance rounding efficiency while minimizing risk and cost.
Keywords: length of stay; family-centered rounds; healthcare costs; clinical decision support system; simulation and modeling